Plasma proteome changes in cardiovascular disease patients: novel isoforms of apolipoprotein A1 - Májek, Pavel; Reicheltová, Zuzana; Suttnar, Jiří; Malý, Martin; Oravec, Milan; Pečánková, Klára; Dyr, Jan E (Journal of translational medicine, 2011)
BACKGROUND: The aim of this proteomic study was to look for changes taking place in plasma proteomes of patients with acute myocardial infarction (AMI), unstable angina pectoris (UAP), and stable angina pectoris (SAP). METHODS: Depleted plasma proteins were separated by 2D SDS-PAGE (pI 4-7), and proteomes were compared using Progenesis SameSpots statistical software. Proteins were identified by nanoLC-MS/MS. Proteins were quantified using commercial kits. Apolipoprotein A1 was studied using 1D and 2D SDS-PAGE, together with western blotting. RESULTS: Reciprocal comparison revealed 46 unique, significantly different spots; proteins in 34 spots were successfully identified and corresponded to 38 different proteins. Discrete comparisons of patient groups showed 45, 41, and 8 significantly different spots when AMI, UAP, and SAP were compared with the control group. On the basis of our proteomic data, plasma levels of two of them, alpha-1 microglobulin and vitamin D-binding protein, were determined. The data, however, failed to prove the proteins to be suitable markers or risk factors in the studied groups. The plasma level and isoform representation of apolipoprotein A1 were also estimated. Using 1D and 2D SDS-PAGE, together with western blotting, we observed extra high-molecular weight apolipoprotein A1 fractions presented only in the patient groups, indicating that the novel high-molecular weight isoforms of apolipoprotein A1 may be potential new markers or possible risk factors of cardiovascular disease. CONCLUSION: The reported data show plasma proteome changes in patients with AMI, UAP, and SAP. We propose some apolipoprotein A1 fractions as a possible new disease-associated marker of cardiovascular disorders.
Keywords: analýza hlavních komponent; proteom; kardiovaskulární nemoci; 2D gelová elektroforéza; Humans; Apolipoprotein A-I; molekulová hmotnost; Female; Aged; senioři; lidé; Principal Component Analysis; apolipoprotein A-I; protein - isoformy; Protein Isoforms; ženské pohlaví; Cardiovascular Diseases; Male; Electrophoresis, Gel, Two-Dimensional; Proteome; mužské pohlaví; Molecular Weight